1998
DOI: 10.1002/(sici)1097-4652(199807)176:1<76::aid-jcp9>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial permeability induced by neutrophil transmigration is potentiated by hypoxia: Role of intracellular cAMP

Abstract: Mucosal tissues, such as the lung and intestine, are primary targets for ischemic damage. Under these conditions, neutrophil (polymorphonuclear leukocyte; PMN) infiltration into the protective epithelium has been implicated as a pathophysiologic mediator. Because PMN transepithelial migration results in increased paracellular permeability, and because our previous data revealed that epithelial hypoxia enhances PMN transmigration, we hypothesized that macromolecular permeability may be altered in epithelium exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Meanwhile, it is known that the MPO activity was markedly relevant to tissue neutrophil accumulation . The endothelial permeability thus increases due to the structure damage of the endothelial cells as well as to the enzymatic cleavage of adherent junction proteins , which eventually results in the transmigration of leukocytes across the endothelial lining into the surrounding tissues and the loss of fluid into extravascular space leading to severe hypoxemia and life‐threatening edema in the lung .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it is known that the MPO activity was markedly relevant to tissue neutrophil accumulation . The endothelial permeability thus increases due to the structure damage of the endothelial cells as well as to the enzymatic cleavage of adherent junction proteins , which eventually results in the transmigration of leukocytes across the endothelial lining into the surrounding tissues and the loss of fluid into extravascular space leading to severe hypoxemia and life‐threatening edema in the lung .…”
Section: Discussionmentioning
confidence: 99%
“…74,118,119 ADM-induced elevation of cAMP has also been reported in epithelial cells, but in these studies a direct effect of ADM-induced barrier function has not been investigated. 120,121 Nevertheless, many other studies have shown that increased cAMP concentrations can improve epithelial barriers, [122][123][124] suggesting that ADM-induced cAMP would contribute to epithelial barrier protection. By contrast, a recent study suggests that ADM may stabilize the epithelial barrier via cAMP-independent mechanisms.…”
Section: Epithelial Barrier Functions Regulated By Adrenomedullinmentioning
confidence: 99%
“…Due to high blood flow under normal conditions, the intestine is particularly susceptible to ischemia and resultant tissue hypoxia (6). It has been shown that ischemia/reperfusion triggers apoptosis in rat intestinal epithelial cells (7).…”
Section: Introductionmentioning
confidence: 99%